3a+5b+7a=
-7a + 3a = -4a
To factorize the expression 7a^2 - 8ab, you need to find the greatest common factor of the two terms. In this case, the common factor is a. So, you can factor out an 'a' to get a(7a - 8b) as the factored form of the expression. This means that 7a^2 - 8ab can be simplified as a multiplied by the quantity (7a - 8b).
7a + 4 = 5a + 7 7a = 5a + 3 2a = 3 a = 3/2
To simplify the expression 6a^2 - 6ab + 7a^2, first combine like terms. Combine the terms with the same variable (a) raised to the same power. This results in 13a^2 - 6ab as the simplified expression. Remember to keep the terms in standard form with the variable term first, followed by any constant terms.
-7a-7b
15
It seems like the question is incomplete, but assuming you meant to ask "What does 6a plus a equal?" In that case, the answer would be 7a, as you are combining like terms by adding the coefficients of the variables. The expression simplifies to 7a because 6a + a = 7a.
7a+a=8a
The relevant expression is 7a.
7a
12a- 6a + a = 7a Since they all have the same variable, you can simply add and subtract 12-6 = 6 6+1 = 7
3a+5b+7a=
91
-7a + 3a = -4a
-2ab
(7a=3)=(-a-5)=16